Indirect effects of urbanization: consequences of increased aggression in an urban male songbird for mates and offspring - Lane, Samuel J.; VanDiest, Isaac J.; Brewer, Valerie N.; Linkous, Courtney R.; Fossett, Taylor E.; Goodchild, Christopher G.; Sewall, Kendra B. (Frontiers in Ecology and Evolution, 2023)
Behavioral traits are often the first response to changing environmental conditions, including human induced rapid environmental change. For example, animals living in urban areas are often more aggressive than rural animals. This is especially evident in songbirds; males of several species display elevated aggression in urban habitats. Increased male aggression has been associated with reduced parental care, but the consequences of this trade-off for males, social partners, and offspring in the context of urbanization remains unclear. We explored the effects of increased urban male aggression on the life history traits, parental care, and offspring outcomes of song sparrows (Melospiza melodia). We predicted that urban males would reduce paternal investment and result in urban females providing greater nestling care or reduced fledging success in urban habitats compared to rural. Contrary to our prediction, aggressive urban males did not decrease care but visited the nest more often compared to rural males. Additionally, urban birds had higher nest and fledging success compared to rural, though this was largely due to higher nest predation in rural habitats. Our study is among the first to evaluate trade-offs associated with elevated aggression expressed by urban animals and adds to a growing body of evidence that urban habitats provide benefits to some species.